Building inspection in the premisses of the State School Professor Rafael Magalhães in Itajubá-MG (Research, Society and Development, 2021)
This work consists in carrying out the building inspection in the State School Professor Rafael Magalhães of Itajubá-MG to which identified the existing pathologies such as: cracks, fissures, cracks, mold, mildew, exposed and spliced electrical wiring, among others, and then a building inspection report was prepared based on the IBAPE (Brazilian Institute of Evaluations and Expert Engineering) standard with the diagnosis and prognosis of each pathological manifestation, and in order to recover the structure a table was generated with a list of priorities for intervention in the building. Through the analysis of the report it was concluded that it is necessary to urgently intervene in the structure with a corrective maintenance, because it presents pathologies that put at risk the physical integrity of the people who live there, besides being an educational building that should have a healthy and safe environment.